Respuesta :
If you would like to know the solution to the equation (x - 2) * (x + 5) = 18, you can calculate this using the following steps:
(x - 2) * (x + 5) = 18
x^2 + 5x - 2x - 10 = 18
x^2 + 3x - 28 = 0
(x + 7) * (x - 4) = 0
1. x = - 7
2. x = 4
The correct result would be x = - 7.
(x - 2) * (x + 5) = 18
x^2 + 5x - 2x - 10 = 18
x^2 + 3x - 28 = 0
(x + 7) * (x - 4) = 0
1. x = - 7
2. x = 4
The correct result would be x = - 7.
The solutions to the equation are x = - 7 and x = 4
What are equation solutions?
Equation solutions are the true values of x in the equation
The equation is given as:
(x - 2)(x + 5) = 18
Expand the equation
x^2 + 5x - 2x - 10 = 18
Subtract 18 from both sides
x^2 + 3x - 28 = 0
Factorize the expression
(x + 7) * (x - 4) = 0
Solve for x
x = - 7 and x = 4
Hence, the solutions to the equation are x = - 7 and x = 4
Read more about quadratic equations at:
https://brainly.com/question/8649555